Risk management practices in information security: Exploring the status quo in the DACH region. Issue 92 (May 2020) - Brunner, Michael; Sauerwein, Clemens; Felderer, Michael; Breu, Ruth
Abstract: Information security management aims at ensuring proper protection of information values and information processing systems (i.e. assets). Information security risk management techniques are incorporated to deal with threats and vulnerabilities that impose risks to information security properties of these assets. This paper investigates the current state of risk management practices being used in information security management in the DACH region (Germany, Austria, Switzerland). We used an anonymous online survey targeting strategic and operative information security and risk managers and collected data from 26 organizations. We analyzed general practices, documentation artifacts, patterns of stakeholder collaboration as well as tool types and data sources used by enterprises to conduct information security management activities. Our findings show that the state of practice of information security risk management is in need of improvement. Current industrial practice heavily relies on manual data collection and complex potentially subjective decision processes with multiple stakeholders involved. Dedicated risk management tools and methods are used selectively and neglected in favor of general-purpose documentation tools and direct communication between stakeholders. In light of our results we propose guidelines for the development of risk management practices that are better aligned with the current operational situation in information security management.